Diet analyses of the pelagic thresher shark, Alopias pelagicus (Lamniformes: Alopiidae), from the Lombok Strait waters, Indonesia - FAQIH AKBAR ALGHOZALI; RAHVANIA SALSABILA; MUHAMMAD WIRALAGA DWI GUSTIANTO; HANIFA MIRANDA IFETPATRIANI HARYO PUTRI; MAHARDIKA RIZQI HIMAWAN; RANNY RAMADHANI YUNENI; CAHYANI KRISNA HATMORO; MARETRA REZKIANI (Society for Indonesian Biodiversity, 2023)
Abstract. Alghozali FA, Salsabila R, Gustianto MWD, Putri HMIH, Himawan MR, Yuneni RR, Hatmoro CK, Rezkiani M. 2023. Diet analyses of the pelagic thresher shark, Alopias pelagicus (Lamniformes: Alopiidae), from the Lombok Strait waters, Indonesia. Biodiversitas 24: 3708-3714. The pelagic thresher shark, Alopias pelagicus, is an endangered shark species estimated to be declining in the Pacific and Indian Oceans because of overexploitation, including from target fisheries and bycatch. Despite its importance in providing better information for species management, the ecological aspects of this species are still rarely studied. This study aims to provide information on the feeding ecology of the pelagic thresher sharks from the Lombok Strait. Stomach samples from 178 specimens were sampled from 2020-2021, and 149 stomachs that contained food contents were analyzed for species diet characterization. Prey Species Accumulation Curve slope values are <0.1 and the percentage of prey coverage for all sharks combined is 92.1%, suggesting reliable inventory in the number of prey represented. The resulting diet indexes suggest that A. pelagicus in Lombok Strait waters is a specialist predator (Ba=0.3) with few prey variations (H=2.21) and no competition between sexes and maturity stages of the species (C=0.64 and 0.81, respectively). The top three prey species found for A. pelagicus in the study area are the Auxis thazard (85.8 %IRI), Sthenoteuthis oualaniensis (8.5 %IRI), and Dasyscopelus spinosus (1.11 %IRI). A better understanding of the overlap of A. pelagicus and its diet, which includes economic fish commodities, will inform authorities to develop better fisheries and conservation management for the species in Indonesia.